The Trust in Influencers in The Beauty Industry Based on the Example of Generation Z - Emilian GWIAŹDZIŃSKI; Aneta OLEJNICZAK (Communications of International Proceedings, 2023)
The objective of this article is to identify the perception of beauty influencers on Instagram by generation Z. The motive behind the study was to fill the research gap, which became apparent after conducting a literature review. The trust factor, considering the SCOPUS database, has not been explored before, particularly from the viewpoint of Generation Z. All the discussed studies were conducted in international markets and involved influencers or focus groups in those regions. However, no study has taken into consideration the Polish market so far. In order to realise the indicated objective, an empirical study was conducted, using an online survey technique, supported by a questionnaire on a sample of 123 individuals selected purposefully, chosen according to age and being part of Generation Z. The study focused on attitudes and opinions about beauty influencers and their activities. In the analysis of the results, it was found that attitudes towards beauty influencers are neutral (ratings fluctuated around the middle of the scale studied). Moreover, representatives of generation Z declared, on average, about 14 times logging into the app per day, which together accounted for about 1.7 hours of daily use of the app. It also turned out that women spent significantly more time on the Instagram platform than men and substantially more often relied on beauty influencers' recommendations than men.
Keywords: influencer marketing; beauty influencer; generation Z; gen Z; Instagram; SNS